Serum uric acid and prognosis in acute ischemic stroke: a dose–response meta-analysis of cohort studies - Zhang, Wenyuan; Cheng, Zicheng; Fu, Fangwang; Zhan, Zhenxiang (Frontiers in Aging Neuroscience, 2023)
Background: There have been contradictory findings regarding the relationship between serum uric acid levels and prognosis in acute ischemic stroke. Whether this association is nonlinear due to uric acid's paradoxical properties (antioxidant and prooxidant) is unclear. Methods: We searched PubMed, Web of Science, and Embase databases until December 2022. Cohort studies reporting serum uric acid levels and functional outcome, mortality, or neurological complications in patients with acute ischemic stroke were included. Summary effect estimates were calculated using a random-effect model. Moreover, dose-response relationships were assessed by the generalized least squares trend estimation. Results: Altogether, 13 cohort studies were identified in this study. Compared to the lowest baseline serum uric acid levels, the highest levels were associated with decreased risk of poor functional outcome (OR = 0.70, 95% CI 0.54–0.91, I2 = 29%), hemorrhagic transformation (OR = 0.15, 95% CI 0.05–0.42, I2 = 79%), and post-stroke depression (OR = 0.04, 95% CI 0.00–0.95, I2 = 89%), but not associated with mortality and symptomatic intracerebral hemorrhage. A nonlinear relationship was observed in poor functional outcome (U-shaped, P for nonlinearity = 0.042), hemorrhagic transformation (inverse, P for nonlinearity = 0.001), and post-stroke depression (inverse, P for nonlinearity = 0.002). In addition, there was a single study reporting a U-shaped association in post-stroke epilepsy (P for nonlinearity < 0.001). Furthermore, another study reported a positive curvilinear association in stroke recurrence (P for nonlinearity < 0.05). The insufficient number of original articles for some prognostic indicators should be considered when interpreting the results of this meta-analysis. Conclusions: In patients with acute ischemic stroke, serum uric acid levels are nonlinearly associated with the risk of poor functional outcome (U-shaped). More evidence is needed to confirm the association between serum uric acid levels and neurological complications following acute ischemic stroke.